2012
DOI: 10.1090/s0002-9947-2012-05780-1
|View full text |Cite
|
Sign up to set email alerts
|

Partial regularity of š‘(š‘„)-harmonic maps

Abstract: Let (g Ī±Ī² (x)) and (h ij (u)) be uniformly elliptic symmetric matrices, and assume that h ij (u) and p(x) (ā‰„ 2) are sufficiently smooth. We prove partial regularity of minimizers for the functional F (u) = Ī© (g Ī±Ī² (x)h ij (u)D Ī± u i D Ī² u j) p(x)/2 dx, under the nonstandard growth conditions of p(x)-type. If g Ī±Ī² (x) are in the class V MO, we have partial Hƶlder regularity. Moreover, if g Ī±Ī² are Hƶlder continuous, we can show partial C 1,Ī±-regularity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…Here, Ragusa-Tachikawa-Takabayashi [13] showed the following lemma on the higher integrability of such local minimizers.…”
Section: Preliminary Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Here, Ragusa-Tachikawa-Takabayashi [13] showed the following lemma on the higher integrability of such local minimizers.…”
Section: Preliminary Resultsmentioning
confidence: 94%
“…For the p(x)-growth case, Ragusa-Tachikawa-Takabayashi [13] showed that a minimizer u of the functional…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study in cooperation by Ragusa and Tachikawa is continued obtaining with Takabayashi, in [25], partial regularity results of minimizers of p(x)-energy functionals.…”
Section: Theorem 22mentioning
confidence: 99%
“…On the other hand, the study of Morrey spaces has received considerable attention in the last thirty years in different research areas (see e.g. [8][9][10]16,17,[19][20][21]23,28,31,36,43]). A further motivation comes from the fact that, to our knowledge, nothing is known concerning Morrey estimates for such operator-valued Fourier multipliers and embedding properties of abstract Sobolev-Morrey spaces.…”
Section: Introductionmentioning
confidence: 99%